The practice of qualitative inquiry in illness narrative scholarship - Warren Bareiss (Qualitative Research in Medicine & Healthcare, 2022)
It has been more than 30 years since Arthur Kleinman first published The Illness Narratives; Suffering, Healing & the Human Condition.1 In his preface, Kleinman referred to the case of a young burn victim: